PERILAKU KEKERASAN YANG DIALAMI OLEH ANAK YANG BERKONFLIK DENGAN HUKUM DALAM MASA REHABILITASI DI LEMBAGA X (STUDI KASUS PADA ANAK R DAN K) - Afri Naswandi; Neri Widya Ramailis (Sisi Lain Realita, 2023)
This study aims to determine how violent behavior is experienced by children in conflict with the law during rehabilitation at institution X (case study of children R and K). A qualitative approach with descriptive methods is applied in this study. Case studies are the main approach in this study to understand the violent behavior experienced by children in conflict with the law during rehabilitation at institution X. Data were collected through observation, in-depth interviews, and documentation. Assisted by analyzing using the theory of violence from Johan Galtung direct violence. The results of the study refer to the violent behavior experienced by children in conflict with the law during rehabilitation at institution X (case study of children R and K) who are the subjects of this study. The forms of violent behavior experienced by R and K are forms of physical and psychological violence where the form of violence occurs due to the emotional outburst of several perpetrators of violence triggered by children running away from institution X during rehabilitation.